Intervensi Gizi Balita pada Wilayah Agrokompleks: Studi Kasus Gampong Peunaga Pasi, Meureubo, Kabupaten Aceh Barat - Fera, Dian; Jihad, Fikri Faidul; Murdani, Ihsan; Fahlevi, Muhammad Iqbal; Musnadi, Jun; Nursia, Lily Eky; Iskandar, Wardah; Siregar, Siti Maisyaroh Fitri; Darmawan, Darmawan (Universitas Teuku Umar, 2025)
This community service project aims to increase the knowledge and awareness of mothers in Gampong Peunaga Pasi regarding the importance of providing nutritious food for toddlers. The activities included socialization, education on the nutritional status of toddlers, and the measurement of toddlers' weight and height using Z-scores to assess nutritional status. The methods used involved lectures, discussions, followed by nutritional status assessments and knowledge evaluation through pre-tests and post-tests. The results showed that of the 15 toddlers measured, 12 had a good nutritional status, while 3 had inadequate nutrition. This initiative successfully enhanced the mothers' understanding of how nutritional status impacts toddler health, with 80% of participants showing improved knowledge after the socialization. Additionally, 90% of mothers reported adopting healthier eating habits for their children. It is recommended that the program be continued, involving more stakeholders to ensure sustained behavioral changes and improve the nutritional health of toddlers in Gampong Peunaga Pasi.